A novel smartphone‐based intervention targeting sleep difficulties in individuals experiencing psychosis: A feasibility and acceptability evaluation. (28th April 2022) - Taylor, Kathryn M.; Bradley, Jonathan; Cella, Matteo
Abstract: Objectives: Cognitive Behavioural Therapy (CBT) is an effective psychological intervention for sleep difficulties and has been used successfully in individuals with psychosis. However, access is restricted due to lack of resources and staff training. Delivering CBT for sleep problems using smartphone technology may facilitate wider access. This study aimed to evaluate the feasibility, acceptability and potential usefulness of a guided, smartphone‐based CBT intervention targeting sleep disturbance for individuals with psychosis. Design: Participants with psychosis spectrum diagnoses were recruited to a single‐arm, uncontrolled study and engaged with the seven‐module programme via smartphone app for six weeks with therapist support. Method: Feasibility was assessed by rates of referral, recruitment and completion. Acceptability was assessed by app usage, a satisfaction questionnaire and qualitative analysis of participants' semi‐structured interview. Pre‐ and post‐intervention assessment of sleep, psychotic experiences, mood, well‐being and functioning was conducted. Mean change confidence intervals were calculated and reported as an indication of usefulness. Results: Fourteen individuals consented to participation, and eleven completed the post‐intervention assessment. On average, each participant engaged with 5.6 of 7 available modules. Qualitative feedback indicated the intervention was considered helpful and would be recommended to others. Suggested improvements to app design were provided by participants. Potential treatment benefits were observed for sleep difficulties, and all outcomes considered, except frequency of hallucinatory experiences. Conclusions: It is feasible and acceptable to deliver therapist‐guided CBT for sleep problems by smartphone app for individuals with psychosis. This method provides a low‐intensity, accessible intervention, which could be offered more routinely. Further research to determine treatment efficacy is warranted.